Certain new integral inequalities involving Erdèlyi-Kober operators - UÇAR, FARUK (Natural Sciences Publishing, 2017)
In the present article, using a family of n positive functions (n ∈ ℕ), the Erdèlyi-Kober integral operator of fractional type is employed to get generalization of certain classes of integral inequalities. As applications, certain special cases and consequent results of the main inequalities obtained in this paper are also discussed. © 2017 NSP.
Keywords: Erdèlyi-Kober operator; Fractional calculus operators; Integral inequalities